THE SEARCH FOR FEMALE EMPOWERMENT THROUGHOUT HISTORY AND COCO CHANEL AS AN ICON OF THE CHANGES IN WOMEN'S LIFE OF 20TH CENTURY - Seabra Rodrigues Martins, Maria Angelica [UNESP] (Unesp-faculdade Ciencias & Letras, 2019)
The cinema and literature has been explored the theme of female empowerment comprehensively: highlighting women's oppression in the relationship of male-female equality in a world dominated by men. In this paper we will observe questions about the achievement of women's rights in the professional, family and personal matter, covering issues of attaining power and social change throughout History. The right vote and birth control, among others, as well as film analysis of the feminine icon of the 20th century, Coco Chanel. As theoretical methodological support will be employed notions of Sociology, History and Theories of Discourse
Keywords: Empowerment; Women's right; Sociology; Discourse theories; Coco Chanel